Analytic model for ZnO-thin film transistor under dark and UV illumination - Mansouri, S.; Bourguiga, R.; Yakuphanoğlu, Fahrettin (Elsevier, 2012)
A ZnO thin film transistor (TFT) was fabricated on a SiO2/Si substrate by sol-gel method. Electrical characteristics of the zinc oxide transistor under various illuminations were analyzed. We have developed a method to extract the TFT parameters under dark and under UV illuminations. This component requires an ohmic source and drain contacts for ideal operation. The performance of electronic-device is often limited by injection. In many real situations, the injection of charge carriers from metals into semiconductors is non-linear. This paper deals with the effects of non-ohmic contacts on the modeling of ZnO thin film transistor and gives specific rules on how to extract the real transistor parameters using only electrical measurements under dark and illumination. We have extracted the TFT parameters using developed method from output characteristics under dark and UV illumination. The drain current of the ZnO thin film transistor under UV illumination is improved. We have demonstrated that the UV illumination reduce the total resistance and improve the performance of the transistor. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: ZnO-TFT; Effect of UV illumination on TFT parameters and performance; Effect of contact resistance; Mobility of charge carriers